Evaluating The Models of Sharia Microfinance in Indonesia: an Analytical Network Process (ANP) Approach - Euis Amalia; Mahmudah Atiqah (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
This study focuses on evaluating the performances of three sharia microfinance models, i.e. cooperative model represented by BMT al Fath, Grameen model represented by MBK, Ltd.co, and mixed model represented by Baytul Amanah Ikhtiar cooperative. ANP approach is used to evaluate the performances of those models from five important aspects (clusters) as the determiners, such as human resource, finance, management, sharia compliance, and marketing. The findings of this research show that the most important aspect (priority) among the clusters is human resource. Thus, the best strategy is the mixed-based; the model which integrates the cooperative system with grameen system. It becomes the best model inasmuch as it implements values of both co ownership and co responsibility, in addition to power of collectivity resulting in no cash collateral.DOI:10.15408/aiq.v7i1.1355